Novel expression and regulation of voltage-dependent potassium (KV7) channels in placentae from women with preeclampsia - Mistry, Hiten D.; McCallum, Laura A.; Kurlak, Lesia O.; Greenwood, Iain A.; Broughton Pipkin, Fiona; Tribe, Rachel M. (American Heart Association, 2011)
Preeclampsia is associated with structural/functional alterations in placental and maternal vasculature. KV7 (voltage-dependant potassium channels encoded by KCNQ1-5 genes) have been detected in several types of blood vessels where they promote vascular relaxation. KV7 channel function can be modulated by KCNE1-5 encoded accessory proteins. The aim of this study was to determine whether KCNQ and KCNE genes are differentially expressed in placentae from women with preeclampsia compared to normotensive controls and to examine any differences in those who delivered preterm (<37 weeks’) or term. Placental biopsies (from midway between the cord and periphery) were obtained, with consent, from White European control (n=24, term) and preeclamptic (n=22; of whom 8 delivered before 37 weeks’) women. KCNQ/KCNE and GAPDH mRNA expression was determined by qRT-PCR. Protein expression/localisation was assessed using immunohistochemistry. KCNQ3 and KCNE5 mRNA expression was significantly up-regulated in preeclampsia (median [IQR]: 1.942 [0.905, 3.379]) versus controls (0.159 [0.088, 0.288]; p=0.001) and exhibited a strong positive correlation with each other (p<0.001) suggesting a novel heterodimer. Enhanced protein expression of KCNQ3 and KCNE5 in preeclampsia was confirmed with localisation mainly restricted to the syncytiotrophoblast. KCNQ4 and KCNE1 isoforms were suppressed in placenta from term preeclamptic women versus controls (p≤0.05). KCNQ1 mRNA expression was increased and KCNQ5 decreased in the preterm preeclamptic group versus controls (p<0.05). In summary, KV7 channels are expressed and markedly modulated in placenta from preeclamptic women. Differential expression of isoforms may lead to altered cell proliferation. The correlation between KCNQ3 and KCNE5 expression is indicative of a novel channel complex and warrants further investigation.